In vivo antioxidant potential of lepidium sativum l. Seeds in albino rats using cisplatin induced nephrotoxicity - Yogesh Chand Yadav,; D.N. Srivastav,; A.K. Seth,; Vipin Saini,; R. Balaraman,; Tejas K. Ghelani, (International Journal of Phytomedicine, 2010)
The present study was designed to investigate to possible potential nephrocurative, nephroprotective activity and in vivo antioxidant potential of 200mg/kg and 400mg/kg ethanolic extract of Lepidium sativum L. seeds was use to against cisplatin (5mg/kg, i.p.) induced nephrotoxicity. The experimental protocol designed as the animals were divided into six groups (n=6) like control, model control, two curative (200mg/kg and 400mg/kg), and two protective groups (200mg/kg and 400mg/kg, were received vehicle, cisplatin, cisplatin + extract, and extract + cisplatin respectively. After 6th days, blood collected from retro-orbital sinus of rats and determined urea and creatinine level in serum of each group after then rats were sacrificed for quantitative estimation of various enzymes and ATPase content in kidney tissue. A single dose of cisplatin induced loss in body weight, increase urine excretion, increased urea & creatinine level in serum; it was significantly recovered by 200mg/kg and 400mg/kg in curative and protective groups. The enzyme estimation in kidney tissue it found that increase malondialdehyde, superoxide dismutase, catalase and reduced glutathione level, it was significantly monitored by 200mg/kg and 400mg/kg in curative and protective groups. These are defined as vivo antioxidant potential. The level of brush border enzymes like Na+ / K+ ATPase, Ca++ ATPase and Mg++ATPase were found significantly reduced after single dose cisplatin injection. It was overcome by treatment of same extract in curative and protective groups. Finally it is concluded that the present study data conformed nephrotoxicity induced by cisplatin due oxidative stress and ethanolic extract of Lepidium sativum L. seeds may have nephroprotective and curative activity.